Do Swiss adolescents perceive the negative effects of their illegal substance use? (Swiss Medical Weekly, 2011)
This study explores adolescents’ perceptions of adverse consequences linked to their illegal psychoactive substance (IPS) use, as they are often thought to minimise them. From a Swiss nationally representative sample of 8740 adolescents aged 16 to 20 pursuing post-mandatory education, 2515 participants reported IPS use in the past month on a self-administered anonymous questionnaire. The percentages of participants reporting problems in four areas (individual, school, relationships and sexual) were assessed, depending on the type of IPS consumption over the last 30 days: occasional cannabis users: ≤2 times; regular cannabis users: ≥3 times; and poly-consumers: cannabis plus at least one other substance used. The percentages varied significantly across these three groups with 26.9% of occasional users, 53.8% of regular users, and 73.3% of poly-consumers reporting at least one problem. Compared to occasional cannabis users, poly-consumers were more likely to report problems in all four categories [relative risk ratio (RRR): 3.38 to 5.44], while regular cannabis users often reported only school and relationship problems [RRR: 2.43 to 3.23]. Thus, many adolescents seem to perceive the negative effects of their IPS use, with heavier consumption being associated with increasing problems. Physicians should feel confident questioning adolescents on the adverse consequences of their IPS consumption, as they are likely to be responsive on this issue.